Development of Learning Media Based on Heyzine Flipbook in The Subject of Lathe Machining Techniques Class XI at SMK Kemala Bhayangkari 1 Jakarta - Berlian Ahmad Fauzi; C Rudy Prihantoro; Hari Din Nugraha (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
This research aims to develop and test the feasibility of products in the form of heyzine flipbook-based learning media in the subject of Lathe Machining Engineering class XI at SMK Kemala Bhayangkari 1 Jakarta. This learning media was developed using the R&D (Research and Development) method using a 4D model consisting of define, design, develop, and disseminate. In the process of assessing the feasibility of this learning media, it provides a validation assessment questionnaire instrument to material experts, media experts, and media feasibility tests to students in grade XI of Machining Engineering as respondents. Learning media is validated by experts with a score of 100% for the material aspect, 94% for the media aspect. And for the results of the feasibility trial, the learning media got a score of 91% of the results of the trial of 53 students. From the results of the test, it can be concluded that the heyzine flipbook-based learning media in the Lathe Machining Engineering class XI subject at SMK Kemala Bhayangkari 1 Jakarta is "Very Feasible" to be used for Lathe Machining Engineering learning activities. The focus of this study is at the stage of development and feasibility testing of the developed media only, as for the results of this study, there are several recommendations that can be given, including the following, heyzine flipbook-based learning media can be implemented and utilized optimally in the learning process of Lathe Machining Engineering at SMK Kemala Bhayangkari 1 Jakarta and other schools where there are Lathe Machining Engineering subjects. And heyzine flipbook-based learning media in the subject of Lathe Machining Engineering needs to be further researched such as the effectiveness of heyzine flipbook-based learning media in the subject of Lathe Machining Engineering.